ANALYSIS OF DYNAMICS OF THE SLAG PARTICLE MOVING SPEED IN GATING SYSTEM - A. N. Chichko; F. S. Lukashevich; S. G. Lihouzov (Литьë и металлургия)
The numerical analysis of dynamics of the cindery particle moving in the system ''riser-gate channel'' is presented. The dependencies of the cindery particle speed on the period of its moving, denseness, radius and proportion of sectional area of riser and feeder are calculated.